Perlindungan Hukum Korban Penipuan Online dalam Transaksi Elektronik di Tinjau dari Hukum Positif Indonesia: Studi Kasus Putusan Nomor 168/Pid.B/2015/PN.Btl - Habibi, Boy Ahmad; Slamet, Sri Redjeki (VISA: Journal of Vision and Ideas, 2026)
The rapid growth of the digital economy has increased online commercial activities while simultaneously amplifying the risk of online fraud, amid ongoing challenges in the effective enforcement of existing legal frameworks. This study examines the criminal law provisions under the Electronic Information and Transactions Law and Law No. 8 of 1999 on Consumer Protection, as well as the role and responsibility of business actors and online marketplaces in protecting victims of online fraud. The research employs a normative juridical method using statutory, case-based (Decision of the Bantul District Court No. 168/Pid.B/2015/PN.Btl), and conceptual approaches, supported by primary, secondary, and tertiary legal materials and qualitative descriptive analysis. The findings indicate that, at the normative level, the ITE Law and the Consumer Protection Law provide a basis for repressive and corrective legal protection; however, their implementation remains inadequate, as law enforcement tends to prioritize the punishment of offenders without effective restoration of victims’ rights, electronic evidence and forensic capacities are still limited, and the operational responsibility of online marketplaces has not been consistently applied. Therefore, regulatory harmonization, strengthening of law enforcement capacity, and the establishment of clear restitution mechanisms are necessary to ensure substantive legal protection for victims of online fraud.